2013
DOI: 10.1136/injuryprev-2012-040658
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from injury: the UK Burden of Injury Multicentre Longitudinal Study

Abstract: A range of factors was found to predict recovery among injured people. These could be used to identify those at risk of delayed recovery and to inform the design of interventions to maximise recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
2
24
1
Order By: Relevance
“…In accordance with previous work [13, 25], we found that most children’s summary HRQoL score had returned to within one standard deviation of baseline by four months post injury. Hospitalization status and age were the only variables associated with a significant change in the rate of recovery, with children who were admitted and older children having a faster rate (steeper slope) to recovery relative to those who were seen in the ED and younger children.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous work [13, 25], we found that most children’s summary HRQoL score had returned to within one standard deviation of baseline by four months post injury. Hospitalization status and age were the only variables associated with a significant change in the rate of recovery, with children who were admitted and older children having a faster rate (steeper slope) to recovery relative to those who were seen in the ED and younger children.…”
Section: Discussionsupporting
confidence: 93%
“…Participants of the UKBOI study (Kendrick et al, 2013), of whom 304 (out of 1517 at baseline) subjects were injured in a road accident, had fully recovered to 28% of respondents at 1 month, 54% at 4 months and 71% at 1 year, which is much higher than in the ESPARR study. However, the results of the ESPARR cohort were coherent with those of the POIS cohort (Wilson et al, 2012) (health status fully recovered for 23% of participants at 5 months and for 36% of participants at 1 year).…”
Section: Interpretation Of Resultsmentioning
confidence: 74%
“…Kendrick et al (2012Kendrick et al ( , 2013 showed that road accidents have generally more consequences at 1 year in terms of health status than other type of user in the UK. Present information related to sequelae is essentially based on the Injury Impairment Scale (IIS (AAAM, 1994)), which is derived from the Abbreviated Injury Scale (AIS (AAAM, 1990)), predicting 1-year post-trauma impairment for each specific lesion.…”
Section: Introductionmentioning
confidence: 98%
“…1 Increased survival rates 3 and reduced lengths of hospital stay 4 are shifting care for injured patients, some of whom have complex needs, into the community. Recovery is often prolonged or incomplete: 5,6 only 49% of injured adults are fully recovered 12 months after injury 7 and two-fifths of working-age adults have not fully returned to work 4 months after injury, with pain, mobility limitations, anxiety, and depression being commonly reported. 8 Discharge home after an injury can be a difficult time and many patients report feeling inadequately prepared.…”
Section: Introductionmentioning
confidence: 99%